A Critical Analysis of Criminal Accomplice Provision in Employment Law Violations - Soleh, Moh; Sarta, Sarta (DiH: Jurnal Ilmu Hukum, 2025)
The increasing use of artificial intelligence (AI), deepfake technology, and advanced medical procedures has transformed the landscape of biometric data, particularly facial features. This study examines the extent to which Indonesia’s Law No. 27 of 2022 on Personal Data Protection (PDP Law) ensures legal certainty for altered biometric facial data, including digitally or medically modified images. Employing a normative juridical research method with statutory and conceptual approaches, the paper interprets legal provisions, evaluates their adequacy, and compares them with international frameworks such as the EU’s General Data Protection Regulation (GDPR) and Singapore’s Personal Data Protection Act (PDPA). Findings reveal that the PDP Law classifies altered facial data as “specific personal data,” mandating explicit consent, robust security measures, and recognition of data subjects’ rights. The law’s extraterritorial scope further extends protection to Indonesian citizens’ data processed abroad. However, enforcement challenges persist, particularly in cross-border contexts and automated profiling. The novelty of this research lies in its focused analysis of altered biometric data as a unique legal category, coupled with comparative insights to address regulatory gaps. The study recommends strengthening implementing regulations, adopting AI-specific safeguards, and enhancing cross-border enforcement cooperation to ensure sustainable protection of biometric privacy in the digital era